Direct Aortic Evolut R Implantation as Valve-In-Valve in a Patient Affected by Leriche Syndrome - Pierre Dahdah; Giuseppe Bruschi; Victor Jebara (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Transcatheter aortic valve implantation (TAVI) is an appropriate therapy to treat elderly patients with severe aortic stenosis considered high-risk surgical candidates. The safety and effectiveness of TAVI have been demonstrated in numerous observational clinical studies, national registries and also in controlled randomized trial [1,2]. The less invasive approach should be considered the transfemoral one, nevertheless a number of patients that are referred for TAVI are not eligible for trans-femoral access due to calcification, vascular narrowing, or tortuosity of ileo-femoral arteries. For them, the transapical, subclavian, or direct aortic approaches may be a suitable alternative. The choice of alternative access should be determined by the heart team based on anatomic characteristics and clinical status of the patient. We report the case of a 75-year-old female affected by Leriche syndrome who successfully underwent valve-in-surgical valve TAVI, through a direct aortic approach, with a Medtronic CoreValve Evolut R.